2001
DOI: 10.1161/hc3901.095933
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Phosphocreatine Depletion by the Creatine Analogue β-Guanidinopropionate Is Associated With Increased Mortality and Loss of ATP in Rats After Myocardial Infarction

Abstract: Background-The failing myocardium is characterized by reductions of phosphocreatine (PCr) and free creatine content and by decreases of energy reserve via creatine kinase (CK), ie, CK reaction velocity (Flux CK ). It has remained unclear whether these changes contribute directly to contractile dysfunction. In the present study, myocardial PCr stores in a heart failure model were further depleted by feeding of the PCr analogue ␤-guanidinopropionate (GP). Functional and metabolic consequences were studied. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 40 publications
1
42
0
Order By: Relevance
“…In the present study, the contractile benefits of CK-M overexpression were observed only in failing heartsboth acutely in response to adrenergic stimulation ( Figure 7 and Supplemental Figure 4) and chronically in terms of functional ( Figure 5C and Figure 6B) and survival improvements ( Figure 5E). Such observations are consistent with prior studies in which longerterm CK inhibition (>40 minutes) impaired in vivo function in normal porcine hearts (42) or resulted in 100% mortality following myocardial infarction in rats (43). Thus, the role of CK is magnified over time and in the failing heart.…”
Section: Figuresupporting
confidence: 91%
“…In the present study, the contractile benefits of CK-M overexpression were observed only in failing heartsboth acutely in response to adrenergic stimulation ( Figure 7 and Supplemental Figure 4) and chronically in terms of functional ( Figure 5C and Figure 6B) and survival improvements ( Figure 5E). Such observations are consistent with prior studies in which longerterm CK inhibition (>40 minutes) impaired in vivo function in normal porcine hearts (42) or resulted in 100% mortality following myocardial infarction in rats (43). Thus, the role of CK is magnified over time and in the failing heart.…”
Section: Figuresupporting
confidence: 91%
“…Inhibitors of CK significantly increase mortality after experimental infarction (16). The reduction in cardiac PCr-to-ATP ratio (PCr/ATP) in experimental postinfarction remodeling is similar to that observed in human heart failure, which, in turn, correlates with clinical severity and predicts overall and cardiovascular mortality (4,10,15,31,34,49).…”
mentioning
confidence: 64%
“…Infarcted, nonviable myocardium lacks PCr and ATP (45,48). In prior 31 P MRS studies (16,18,19,32,33,37) of infarcted rodent hearts, the detected PCr and ATP signals were attributed to the surviving viable regions, even when the entire infarcted region was contained within the region studied by MRS. Based on this accepted practice and our efforts through animal positioning and slice selection to minimize infarcted tissue within the volume of interest, the cardiac PCr/ATP values reported here derive almost entirely from surviving, viable myocardium. Data were compared by ANOVA with STATISTICA software (StatSoft, Tulsa, OK).…”
Section: In Micementioning
confidence: 95%
See 1 more Smart Citation
“…80 Another is the example shown studying myocardial infarction in the rat. 81 Myocardial [PCr] and CK reaction velocity were decreased by Ϸ90% and [ATP] by 18% (a profile similar to the heart failure phenotype) in rats fed with the creatine analog ␤-guanidinoproprionic acid, a competitive inhibitor of creatine transport and the CK reaction. Unlike control rat hearts that survived acute myocardial infarction, the 24-hour mortality of rats with severely compromised CK-PCr system was 100%.…”
Section: Increased Susceptibility Of the Hypertrophied And Failing Hementioning
confidence: 99%